MEMBANGUN LEARNING SOCIETY DI PERGURUAN TINGGI MELALUI PERPUSTAKAAN - Basuki, Basuki (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
The strategic changes undertaken by the Ministry of National Education related with strategic planning program for college will result in any consequences, for instance the shift of vision and mission, the output goal, the arrangement of organization until the issue of standardization in all fields. One of the most important elements to note is that the standardization of the library quality. The purpose of the strategic plan is aimed at improving the quality of educational process conducted by university in order to create educated students who have good competences and intelligences to take bright action and full of responsibility. Those requirements are compulsory to be considered in carrying out duties on specific occupations to meet with the society needs. One of indicators of qualified and standardized library is that its optimum contribution on developing community learning in the college. This article tries to examine some concepts of creating community learning in college setting through revitalizing the role of library. This is in accordance with the presence of library in every college that occupies more strategic position, urgent and vital to the dynamics and progression of the college itself. Library is the main genuine indicator of the progress of a good college.Â ÙØ¹ØªØ¨Ø± Ø§ÙØ§Ø³ØªØ±Ø§ØªÙØ¬Ù Ø§ÙØ°Ù ÙØ§ÙØª Ø¨Ù ÙØ²Ø§Ø±Ø© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙØ© Ø§ÙÙØªØ¹ÙÙØ© Ø¨Ø§ÙØ¨Ø±Ø§ÙØ¬ Ø§ÙØ§Ø³ØªÙØ±Ø§ØªÙØ¬ÙØ© ÙÙÙØ±ØÙØ© Ø§ÙØ¬Ø§ÙØ¹ÙØ© Ø³ØªÙØªØ¬ ÙÙÙ Ø§ÙÙØ³Ø¨Ø¨Ø§Øª Ø§ÙØ®Ø§ØµØ©Ø ÙÙÙØ§ ØªØºÙÙØ± Ø§ÙØ±Ø¤ÙØ© ÙØ§ÙØ±Ø³Ø§ÙØ© ÙØ§ÙØ£ÙØ¯Ø§Ù ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø© ÙØªÙØ¸ÙÙ Ø§ÙØ¥Ø¯Ø§Ø±Ø© Ø§ÙØ¬Ø§ÙØ¹ÙØ© ØØªÙ ÙØ¶Ø¹ Ø§ÙØ®Ø·Ø· Ø§ÙÙØ¹ÙØ§Ø±ÙØ© ÙÙ Ø¬ÙÙØ¹ Ø§ÙÙÙØ§ØÙ. ÙÙÙ Ø£ÙÙ ÙØ°Ù Ø§ÙØ¬ÙØ§ÙØ¨ ÙØ¶Ø¹ Ø§ÙØ®Ø·Ø© Ø§ÙÙØ¹ÙØ§Ø±ÙØ© ÙÙ ÙÙØ¹ÙØ© Ø§ÙÙÙØªØ¨Ø©. ÙØ°Ø§ Ø§ÙÙØ¯Ù Ø§ÙØ§Ø³ØªÙØ±Ø§ØªÙØ¬Ù ÙØ±ØªØ¨Ø· Ø¨ÙÙØ¹ÙÙØ© Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¬Ø§ÙØ¹ÙØ©Ø Ø§ÙØªÙ Ø¨ÙØ§ ÙÙØ¯Ø± Ø§ÙØ·Ø§ÙØ¨ Ø§ÙØ®Ø±ÙÙØ¬ Ø¹ÙÙ Ø£Ø¯Ø§Ø¡ Ø¹ÙÙ ÙØ§ ÙØ´Ø±Ø· ÙÙØ¹ØªØ¨Ø± ÙØ§Ø¯Ø±Ø§ Ø¹ÙØ¯ Ø§ÙÙØ¬ØªÙØ¹ ÙØ£Ø¯Ø§Ø¡ ÙØ³Ø¤ÙÙÙØ© ÙØ§ ÙÙÙ. ÙÙÙ Ø§ÙÙØ¤Ø´Ø±Ø§Øª ÙÙ ÙÙØ¹ÙØ© Ø§ÙÙÙØªØ¨Ø© Ø§Ø³ÙØ§Ù Ø§ÙÙÙØªØ¨Ø© ÙÙ ØªÙÙÙÙ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹ÙÙÙ ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø©. ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¯Ø±Ø§Ø³Ø© Ø¨Ø¹Ø¶ Ø§ÙÙÙØ§ÙÙÙ ÙÙ Ø¥ÙØ´Ø§Ø¡ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹ÙÙÙ ÙÙ Ø§ÙØ¬Ø§ÙØ¹Ø§Øª Ø¹Ù Ø·Ø±ÙÙ Ø§ÙÙÙØªØ¨Ø©Ø ÙÙÙØ§ÙØªÙØ§ Ø§ÙÙØ§ÙØ© ÙÙ ØªØ·ÙÙØ± Ø§ÙØ¬Ø§ÙØ¹Ø© ÙÙÙ Ø¹ÙØµØ± ÙØ§Ù ÙÙ ØªÙØ¯ÙÙÙØ§.